2014
DOI: 10.1002/aoc.3122
|View full text |Cite
|
Sign up to set email alerts
|

Sn‐mediated one‐pot four‐component allylation of aldimines

Abstract: A convenient and facile method for the synthesis of homoallylic amines was disclosed. The one-pot reaction of aldehydes, aromatic amines and allylic bromide with tin powder at room temperature could afford the homoallylic amines in good to excellent yield without any promoter or additive. The method is highly efficient and environmentally benign with low cost and concise manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…[58][59][60] In our previous investigation, we found tin powder could promote onepot allylation reactions of aldehydes, amines and allylic bromide in 1,4-dioxane to give homoallylic amines in good yields. [61] In our on-going studies, we found that acylhydrazines could replace amines in a similar reaction using water as solvent. In particular, acylhydrazines could react not only with aldehydes but also with less reactive ketones to afford N′-homoallylic hydrazides, which are relatively new scaffolds found in a wide variety of biologically active molecules, [62][63][64] and also show potential applications in material science (Scheme 1).…”
Section: Introductionmentioning
confidence: 88%
“…[58][59][60] In our previous investigation, we found tin powder could promote onepot allylation reactions of aldehydes, amines and allylic bromide in 1,4-dioxane to give homoallylic amines in good yields. [61] In our on-going studies, we found that acylhydrazines could replace amines in a similar reaction using water as solvent. In particular, acylhydrazines could react not only with aldehydes but also with less reactive ketones to afford N′-homoallylic hydrazides, which are relatively new scaffolds found in a wide variety of biologically active molecules, [62][63][64] and also show potential applications in material science (Scheme 1).…”
Section: Introductionmentioning
confidence: 88%
“…This technique avoided the use of toxic stannanes while retaining their merits such as moisture stability, tolerance to functional groups and high selectivity . Hence, some research works on tin‐promoted reactions have been conducted by our group . However, all of them were only focused on racemic allylations and lactamizations.…”
Section: Introductionmentioning
confidence: 99%
“…Because of some advantages of tin-metal-promoted reactions, we are interested in tin-promoted organic reactions, and have found that tin-mediated one-pot allylation of aldehydes, amines and allyl bromide gives the homoallylic amines chemoselectively without the formation of homoallylic alcohols from allylation of the aldehydes or allylic amines from allylation of the amines (Scheme 1, a). 28 However, this method cannot be applied to ketones; if ketones are used instead of aldehydes under the same conditions, allylation of the amines to give allylic amines is the major reaction (Scheme 1, b).…”
mentioning
confidence: 99%